PENGGUNAAN BANK KONVENSIONAL PADA BAZNAS KOTA SOLOK - Roki Ade Deswan; Rizal Fahlefi; Zainuddin Zainuddin (IAIN Batusangkar, 2019)
In dealing with conventional financial institutions as already stated in the Fatwa MUI No. 1 year 2004 on Interest is: For the existing office / network of islamic financial institutions and easily accessible, it is not permissible to perform the transaction based on the calculation of interest. For the region that there has been no office / network of islamic financial institutions, permitted to conduct transactions in conventional financial institutions based on the principles of emergency / lavatory. BAZNAS Solok city in the management of zakat is still using the conventional banks while the islamic banks already exist in the City of Solok. The purpose of this study is to find out why BAZNAS Solok City use conventional banks and to find out and analyze the law against BAZNAS Solok City use conventional banks. The use of conventional bank on BAZNAS Kota Solok caused because conventional banks have been there on the previous management, the Salaries of Civil Servants in the environment government of the City of Solok also through nagari bank conventional, and Employees of nagari bank direct tithe to the BAZNAS Solok City, If moved bank feared not collected zakat is derived from the employees of conventional banks.